The competitive game theory of Norbert Elias as alternative to the reading of public policies for sport and leisure in Brazil - Starepravo, Fernando Augusto; Souza, Juliano de; Marchi Junior, Wanderley (Brazilian journal of physical education and sport, 2012)
The mapping of recent scientific literature on public policy of sport and leisure in Brazil has presented a set of productions, which are mostly works in progress, with the predominance of empirical exhibitions, with well-defined methodological procedures, but they have not been presented a consistent dialogue with the literature. In studies showing greater theoretical consistency, the authors usually adopt a critical stance to neoliberalism, understanding that this model, based on the interests of capital, leads the State to intervene less in the social, transferring this function to civil society organized sectors. Given this situation slightly raised and trying to expand it, we present in this article a possibility of reading the public policy of sport and leisure, supported the theoretical and methodological assumptions of Norbert Elias' Game Theory Competitive.